CAREER WOMEN AND DAKWAH - Intan Qurratulaini (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2018)
Women who have multiple roles in the society known as "the" career woman "'. Various conditions of life faced, including the increase of the quality of education of women, leads to the rise of woman role in the public sphere, either as a part of her self-actualization or due to economic demands to support her family. However, the multi-role of women is still a matter of controversy in the community. Thus, the clarification is necessary to correct the perceptions between domestic and public functions and their relations to women actual function as caliphs in the earth, where they have an equal role with men in terms of amar ma 'ruf nahi mungkar, that is spreading the da’wah values in the society. This will be the main focus of this paper.